Biological Control of soft rot bacteria of onion in Bangladesh - Rahman, MM; Khan, AA; Akanda, AM (Bangladesh Journal of Scientific and Industrial Research, 2021)
An investigation was conducted to search antagonistic bacteria as biological control agents of soft rotting bacterial pathogen of onion (Allium cepa L.) in vitro and in storage. Antibacterial activity of previously isolated 91 bacterial isolates was tested in vitro against onion soft rot bacteria Burkholderia cepacia O-15. Two isolates namely, R-15 and E-37 were found antagonistic against onion soft rot bacteria. Isolate R-15 was identified as the genus Bacillus and the isolate E-37 to Lactobacillus sp. Isolate R-15 proved to be a strong antagonist against onion soft rot bacteria was selected for bio-control of onion in storage. That was also effectively reduces the soft rot disease of onion in storage condition. Percentage of disease reduction (PDR) due to treatment with antagonistic bacteria was 72.4% compared to untreated control. It is therefore suggested that this isolate could be exploited as biocontrol agent for onion soft rot in Bangladesh. Bangladesh J. Sci. Ind. Res.56(4), 231-240, 2021